Reviving Plecoptera research in Pakistan after five decades: faunistic review and redescription of Mesonemoura skardui (Aubert, 1959) - Rehman, Abdur; Huo, Qing-Bo; Zia, Ahmed; Iqbal, Toheed; Du, Yu-Zhou (Zootaxa, 2026)
Stoneflies (Plecoptera) are vital bioindicators of freshwater health, playing a foundational role in stream ecosystems worldwide. Despite their ecological significance, Pakistan’s stonefly fauna remains largely unexplored, presenting an untapped frontier for biodiversity research. Positioned at the convergence of the Palearctic and Oriental realms, Pakistan’s diverse landscapes from the towering peaks of the Hindu Kush and Karakoram to the western Himalayas, offer rich, largely unstudied habitats for aquatic species. This study aims to revive interest in Plecoptera research by providing a comprehensive review of species distributions across Pakistan, including an extensive literature survey and the redescription of Mesonemoura skardui (Aubert, 1959). The study highlights the significance of local Plecoptera research while enhancing a global understanding of this country’s fauna. The Plecoptera fauna of Pakistan comprises six families, 10 genera, and 20 documented species. This research presents a species checklist, distribution map, and identification key for adult families and genera, with the Nemouridae family being the most species-rich, particularly in Khyber Pakhtunkhwa province, which emerges as a hotspot for stonefly diversity. Beyond documenting current species, the study identifies research gaps and proposes strategies to further explore Pakistan’s Plecoptera fauna. As the first major study of its kind in > 50 years, this work revitalizes interest in the region’s stonefly diversity and lays a foundation for future research, offering a pathway for ongoing exploration and conservation of this essential insect group.